Toward hip-hop pedagogies for music education. (May 2016) - Kruse, Adam J.
Music education scholarship in the areas of popular, vernacular, and participatory musicianship has grown in the past decades; however, music education research concerned specifically with hip-hop has been relatively scarce. Because hip-hop music can differ tremendously from the traditional western genres with which many music educators are most familiar, a great need for research in this area exists. In this article, I summarize general education scholarship related to hip-hop and offer implications toward hip-hop pedagogies for music education. I employ Hill's (2009) classifications of hip-hop pedagogy ( Pedagogies with hip-hop, Pedagogies about hip-hop, and Pedagogies of hip-hop ) as a structure to better understand previous literature and to provide a descriptive framework for potential applications of hip-hop pedagogies to music education settings. I describe Hill's categories using the labels of Hip-hop as a bridge, Hip-hop as a lens, and Hip-hop as practice .